The Impact of Social Media Influencers on Personal Finance and Investment Decisions: Case Study of Students of The IAI Uluwiyah Mojokerto Sharia Economics Program - Nur Masithoh, Fitria (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This research aims to explore the impact of social media influencers on the personal financial behavior and investment decisions of Sharia Economics Study Program students at IAI Uluwiyah Mojokerto. The focus of this research is to understand motivations for following financial influencers, changes in financial behavior after following influencers, and reasons for choosing sharia-based investments. This research uses a phenomenological method with a case study approach. Data was collected through in-depth interviews with students who follow financial influencers on social media. Data analysis was carried out using coding techniques to identify the main themes that emerged from participants' experiences. The research results show that students are motivated to follow financial influencers because they are looking for information and education, inspiration, and the influencer's credibility. After following influencers, students show increased savings discipline, reduced consumer spending, and wiser investment decisions. Students choose sharia investments because of adherence to religious principles, transparency and fairness, as well as the potential for competitive profits.